أزمات الأسهم وسلوك السوق: حالة سوق الأسهم السعودية - Al-Twaijry, Abdulrahman (مجلة العلوم الإدارية و الإقتصادية, 2011)
The Saudi stock market is more than 25 years old, and since its birth in 1985 and until 2005, there has been no major collapse. However, during the last few years (2006 – 2009), the market has witnessed two crises, the first is a major one and the second is minor. The purpose of this research is to determine the impact of the 2006 stock crisis on the stock market behavior and examine the effect of this crisis on stock prices and stock returns using three models (financial, economic and accounting). The comparison and regression results reveal that stock market behavior did change after the crisis. The financial model has been heavily affected by the crisis (adjusted R2 declined from 0.41 to 0.15 only after the crisis), whilst the economic model has only slightly changed (adjusted R2 was 0.61 before the crisis and 0.62 after it). The accounting model was also affected by the 2006 crisis, but not significantly. Even though the power of the model was lower after the crisis, it remained high and significant.